2005
DOI: 10.1111/j.1469-8137.2005.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Taking mycocentrism seriously: mycorrhizal fungal and plant responses to elevated CO2

Abstract: Summary• The aim here was to separately assess mycorrhizal fungal and plant responses under elevated atmospheric CO 2 , and to test a mycocentric model that assumes that increased carbon availability to the fungus will not automatically feed back to enhanced plant growth performance.• Meta-analyses were applied across independent studies. Responses were compared in ectomycorrhizal (ECM) and arbuscular mycorrhizal (AM) fungi, and ECM and AM plants.• Responses of both mycorrhizal fungi and mycorrhizal plants to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(147 citation statements)
references
References 92 publications
3
141
3
Order By: Relevance
“…The trees with the finest roots 50.5 mm in diameter had performed also increased ectomycorrhizal abundance ) that might influence root architecture. In numerous experiments, CO 2 enrichment elicited an increase in the degree of ectomycorrhizal colonization as well as changes in the morphotype assemblages (Godbold & Berntson, 1997;Treseder, 2004;Alberton et al, 2005). Increased root length and thickening of diameter (Janssens et al, 1998, Pritchard et al, 2001) along with enhanced storage of starch in fine roots (Janssens et al, 1998) has been observed under CO 2 enrichment.…”
Section: Specific Root Length As a Stress Indicatormentioning
confidence: 99%
“…The trees with the finest roots 50.5 mm in diameter had performed also increased ectomycorrhizal abundance ) that might influence root architecture. In numerous experiments, CO 2 enrichment elicited an increase in the degree of ectomycorrhizal colonization as well as changes in the morphotype assemblages (Godbold & Berntson, 1997;Treseder, 2004;Alberton et al, 2005). Increased root length and thickening of diameter (Janssens et al, 1998, Pritchard et al, 2001) along with enhanced storage of starch in fine roots (Janssens et al, 1998) has been observed under CO 2 enrichment.…”
Section: Specific Root Length As a Stress Indicatormentioning
confidence: 99%
“…2003) and roots and associated symbionts can respond differently to environmental change (Alberton et al. 2005; Vega‐Frutis et al. 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mycorrhizal fungi have a physiology and chemistry very different to those of plant roots (Smith & Read, 1997) and therefore may respond independently to changes in climate and plant production. A meta-analysis of laboratory and field CO 2 enrichment studies using temperate plants has shown that plants consistently allocate more C to mycorrhizal fungi under elevated CO 2 and nutrient-limiting conditions (Alberton et al, 2005). Therefore, in a world with elevated concentrations of atmospheric CO 2 , there may be significant increases in the allocation of C to AMF in tropical forests, which generally grow on nutrient-poor soils (Vitousek & Sanford, 1986), and which already appear to be increasing in productivity, probably in response to raised concentrations of atmospheric CO 2 (Phillips et al, 2008).…”
Section: Mycorrhizal Mycelial Respiration In Moist Tropical Forests Amentioning
confidence: 99%
“…Soil CO 2 efflux arises from the activity of a wide variety of belowground organisms, but only two sources have been assessed in tropical forests: (1) 'autotrophic respiration', derived from roots, arbuscular mycorrhizal fungi (AMF) and the metabolism of root exudates by microorganisms inhabiting the rhizosphere, and (2) 'heterotrophic respiration', derived from microbial decomposition of plant detritus and soil organic matter (Hanson et al, 2000). Respiration from roots and that from AMF are almost always assessed together as a single source of respiration (Hanson et al, 2000;Subke et al, 2006), yet their assessment as distinct sources is required given that they may respond somewhat independently to environmental change (Alberton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%